1976
DOI: 10.1002/hlca.19760590113
|View full text |Cite
|
Sign up to set email alerts
|

Ammoniakverlust aus α,ω‐Alkandiaminen im Massenspektrometer. 22. Mitteilung über das massenspektrometrische Verhalten von Stickstoffverbindungen

Abstract: Loss of ammonia from a, w-alkanediamines in the mass spectrometer. -Sunzmary.Under electron impact cc, w-alkanediamines lose ammonia from the molecular ion. This Iragmentation reaction is explained in the case of 1.4-butanediamine (1) on the basis of thc spcctra of homologues and deuteriated derivatives. The reaction proceeds via neighbouring group participation; the mechanism is given in Scheme 1. Fig. 2) und 1,12-Dodecandiamin (3, Fig. 3) abgebildet. Ein Vergleich der Intensitatswerte fur die [ M -NH3]-Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
(2 reference statements)
0
13
0
Order By: Relevance
“…The [M Ϫ NH 3 ] ؒϩ ions generated from 1,4-diaminobutane and 1,5diaminopentane react with dimethyl disulfide, but the absence of ؒ SCH 3 abstraction contradicts a previous suggestion of a distonic ion structure. 19 Additionally, CID experiments indicated that the radical cations had acyclic structures, in contrast to previous proposals. 19 Reaction of CH 5 ϩ with diamines led to the formation of cyclic [M ϩ H Ϫ NH 3 ] ؒϩ (Scheme 1).…”
Section: B Radical Cation Reactionsmentioning
confidence: 73%
See 1 more Smart Citation
“…The [M Ϫ NH 3 ] ؒϩ ions generated from 1,4-diaminobutane and 1,5diaminopentane react with dimethyl disulfide, but the absence of ؒ SCH 3 abstraction contradicts a previous suggestion of a distonic ion structure. 19 Additionally, CID experiments indicated that the radical cations had acyclic structures, in contrast to previous proposals. 19 Reaction of CH 5 ϩ with diamines led to the formation of cyclic [M ϩ H Ϫ NH 3 ] ؒϩ (Scheme 1).…”
Section: B Radical Cation Reactionsmentioning
confidence: 73%
“…19 Additionally, CID experiments indicated that the radical cations had acyclic structures, in contrast to previous proposals. 19 Reaction of CH 5 ϩ with diamines led to the formation of cyclic [M ϩ H Ϫ NH 3 ] ؒϩ (Scheme 1). 18 Similar results were obtained by Bouchoux et al, 20 who found that protonated amino alcohols undergo intramolecular nucleophilic substitution upon activation.…”
Section: B Radical Cation Reactionsmentioning
confidence: 73%
“…One can also suppose that different molecular ions behave differently with regard to the exchange of the hydrogen atoms of the amino groups prior to the fragmentation. EXPERIMENTAL 1,6-Diamimhexane-l,1 ,6,6-d4 (2). Dimethyladipate was reduced in tetrahydrofuran by LiAlD4 in 1,6-hexanediol-1,1,6,6-d4 (60% yield).…”
Section: Resultsmentioning
confidence: 99%
“…Within the same cooperation many years later the elimination of ammonia from the molecular ions of 1,4‐diaminobutane and 1,5‐diamino‐pentane was studied using collision‐induced dissociation and ion/molecule reactions, the latter being performed with use of the Bruker FTICR mass spectrometer mentioned in Subsection VII B . The motivation was that the $[{\rm M} - {\rm NH}_3 ]^{ + \bullet }$ ion from 1,4‐diaminobutane had been suggested to be the interesting ring‐closed α‐distonic ion of pyrrolidine (Mayerl & Hesse, 1976). However, the $[{\rm M} - {\rm NH}_3 ]^{ + \bullet }$ ion from neither 1,4‐diaminobutane nor 1,5‐diaminopentane behaved like a distonic ion in reactions with dimethyl disulfide (Fernandes et al, 2002), known to be an excellent substrate to identify distonic ion structures by a unique ${\rm CH}_3 {\rm S}^ \bullet $ abstraction (Stirk, Kiminkinen, & Kenttämaa, 1992).…”
Section: The Years Of Reversed Geometry Double Focusing Hybridmentioning
confidence: 99%